Impact of water chemistry, shelf-life, and regeneration in the removal of different chemical and biological contaminants in water by a model Polymeric Graphene Oxide Nanocomposite Membrane Coating. (December 2019) - Bandara, Pasan Chinthana; Nadres, Enrico Tapire; Peña-Bahamonde, Janire; Rodrigues, Debora F.
Graphical abstract: Highlights: Water chemistry impacts significantly the removal of different contaminants. Duration of storage can lead to reduced performance of the coating. Acidic and basic pH affected the active sites for microbial and nitrate removals. High salinity impacted nitrate removal but not heavy metal or microbial removals. Hardness showed an inhibitory role for Cr(VI) and nitrate removals. Abstract: The present study aims to investigate the impact of water chemistry, shelf-life and regeneration of a previously developed chitosan (CS)-polyethyleneimine (PEI)-graphene oxide (GO) nanocomposite membrane coating. Several studies have shown the development of coatings with multifuctionality in DI water but have negleted the effects of water chemistry, shelf-life and chemical regeneration of these nanocomposite coatings for the simultaneous removal of different biological and chemical water contaminants. This nanocomposite was selected for this investigation since it showed a broad removal capability. This nanocomposite showed removals of Cr(VI), Cu(II), and Pb(II) over 90% at 1 ppm initial concentration and nitrate >75% at 20 ppm initial concentration under DI water. Furthermore, the coated filters were effective in removing >3 logs of E. coli K12, B. subtilis, and P. aeruginosa . The integrity and performance of the modified filters were investigated against a wide range of water chemistries with different pH values, salinity, and total hardness. For water chemistries with pH 4–9, salinity 50–1000 ppm, and total hardness of 50–500 ppm as CaCO3, at least one tested contaminant showed similar percentage removals indicating the potential use of the modified filters in these large ranges of water chemistry conditions. Based on that, the filters were used to treat representative samples of wastewater and seawater. The coated filters were able to remove suspended particles, bacteria, and heavy metals effectively. Later the potential for regeneration and the shelf-life of the coated filters were also investigated. For the regeneration, only 0.1 M HCl was able to desorb up to 40% of the adsorbed heavy metal, indicating that the filter can be partially regenerated. Accelerated experiments of shelf-life demonstrated that the modified filters lose their optimum performance around 9–12 months, indicating their potential for short-term storage without any specific preservation conditions.